BODY WEIGHT, MUSCLE WIGHT, PROTEIN, DNA AND RNA CONTENTS IN BREAST MUSCLE (M. Pectoralis Major) OF SELECTED LOCAL MEAT CHICKEN FED ON A DIFFERENT LEVEL OF KIAPU (Pistia stratiotes L.) IN FERMENTED DIET - M. Aman Yaman; Sri Jeksi; Muhammad Daud (Jurnal Kedokteran Hewan, 2022)
The study to evaluate changes in body weight, muscle weight, muscle protein content and total DNA and RNA on breast muscle of selectedlocal chicken due to different levels of fermented feed containing Kiapu (Pistia stratiotes L.) was conducted using a factorial randomized designfor 7 weeks. This study used 72 selected local chickens, which were separated into 2 groups (male and female) and fed on 3 types of feedtreatment, namely P0 (control treatment with 100% commercial feed), P1 (80% commercial feed + 20% fermented Kiapu feed), and P2 (70%commercial feed + 30% fermented Kiapu feed). Parameters were body weight, muscle weight, muscle protein content and total DNA and RNAon breast muscle of chicken. Total protein, DNA and RNA content were analysed by enzymatic reactions of prokaryotic cell and measured with aUV-Spectrophotometer according to the specified OD (optical density). The results showed that feeding Kiapu fermented 20-30% increased bodyweight and protein content of breast muscle of female chicken by change in DNA content. However, the feeding treatment had no changes inmuscle weight and RNA content of both in male and female chicken. On the other hand, substitution of 20-30% Kiapu fermented feed causednegative changes in DNA level of breast muscle. From this study, it was concluded that substitution of fermented feed containing 20-30% Kiapuassociated with the growth process of breast muscle protein is suitable for female but not suitable for male chicken.